Expression of CXCR4 on T-cell subsets and Plasma IL-17 Concentrations in Patients with Aplastic Anaemia - Qian Niu (Nature Portfolio, 2017)
Abstract Acquired aplastic anaemia (AA) is caused by T-cells migrating to and attacking bone marrow (BM) in response to chemokines (e.g., CXCR4). We investigated CXCR4 expressions on circulating T-cell subsets, plasma IL-17A concentrations, and their correlations with AA manifestations. We enrolled 71 patients with acquired AA (36 severe AA cases [SAA] and 35 non-severe AA cases [NSAA]) and 42 healthy volunteers. We used flow cytometry and ELISA to measure circulating CD4+ and CD8+ T-cells, their CXCR4 expressions, and plasma IL-17A concentrations. Compared to the healthy controls, SAA patients had fewer peripheral CD4+ T-cells, more CD8+ T-cells, and a significantly decreased CD4+/CD8+ ratio which was positively correlated with AA manifestations. Patients with SAA or NSAA had higher proportions of CD4+CXCR4+ and CD8+CXCR4+ T-cells, which were negatively correlated with haemoglobin concentrations and absolute neutrophil counts. Patients with SAA or NSAA had higher plasma IL-17A concentrations, which were negatively correlated with AA manifestations and the CD4+/CD8+ ratio. IL-17A concentrations showed a very week correlation with CD4+CXCR4+ T-cells frequencies, and no correlation with CD8+CXCR4+ T-cells frequencies. Aberrant CXCR4 expression may allow circulating T-cells, especially CD8+ T-cells, to infiltrate BM during AA progression. Elevated IL-17A concentrations may contribute to AA progression outside of the CXCR4-SDF-1α axis.